PENERAPAN MODEL LEARNING CYCLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SIFAT-SIFAT CAHAYA - Munawaroh, Ai Nani; Jayadinata, Asep Kurnia; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2017)
This research based on the results of preliminary observation on learning natural science in class V SDN Cinangsi, it is known that student learning outcome on the material nature of light is still very low. This is because the teachers only used lecture methods in performing learning. Therefore, this research is conducted by applying learning cycle model on the material nature of light. This research is a Class Action Research (PTK). This research used design of Kemmis and Mc. Taggart. Instruments used in the research are guidance of teacher planning and performance observation,Â guidance of student activity observation, interview guidance, notes field format, and evaluation questions. Student learning outcomes when preliminary data only reached 22.6%, cycle I achieve 54.8%, cycle II 80.6%, and cycle III reach 94%. Thus, can be concluded that the learning cycle model can improve the learning outcom of students on material nature of light.